\magnification 2200 \parindent 0pt \parskip 10pt \pageno=1 \hsize 7truein \hoffset -0.35truein \vsize 9.2truein \def\u{\vskip -5pt} \def\v{\vskip 10pt} Linear algebra pre-requisites you must know. ${\bf b_1, ..., b_n}$ are linearly independent if \u $c_1{\bf b_1} + c_2{\bf b_2} + ... + c_n{\bf b_n} = d_1{\bf b_1} + d_2{\bf b_2} + ... + d_n{\bf b_n}$ \centerline{implies $c_1 = d_1$, $c_2 = d_2$..., $c_n = d_n$.} or equivalently, ${\bf b_1, ..., b_n}$ are linearly independent if \u $c_1{\bf b_1} + c_2{\bf b_2} + ... + c_n{\bf b_n} = 0$ implies $c_1 = c_2 = ... c_n$. \v\v Example 1: ${\bf b_1} = (1, 0, 0)$, ${\bf b_2} = (0, 1, 0)$, ${\bf b_3} = (0, 0, 1)$. \v \centerline{$(1, 2, 3) \not= (1, 2, 4)$.} \v \centerline{If $(a, b, c) = (1, 2, 3)$ then $a = 1$, $b = 2$, $c = 3$.} \v\v Example 2: ${\bf b_1} = 1$, ${\bf b_2} = t$, ${\bf b_3} = t^2$. \v \centerline{$1 + 2t + 3t^2 \not= 1 + 2t + 4t^2$.} \v \centerline{If $a + bt + ct^2 = 1 + 2t + 3t^2$ then $a = 1$, $b = 2$, $c = 3$.} \eject Application: Partial Fractions ${ 4\over (x^2 + 1)(x - 3)} = {Ax + B \over x^2 + 1} + {C \over x - 3}$ $\hskip .7in = {(Ax + B)(x-3) + C(x^2 + 1) \over (x^2 + 1)(x - 3)}$ Hence ${ 4\over (x^2 + 1)(x - 3)} = {(Ax + B)(x-3) + C(x^2 + 1) \over (x^2 + 1)(x - 3)}$ \v \centerline{Thus $4 = (Ax + B)(x-3) + C(x^2 + 1)$} \v \centerline{$ {4 = Ax^2 + Bx - 3Ax - 3B + Cx^2 + C}$} \v \centerline{${4 = (A + C)x^2 + (B - 3A)x - 3B + C }$} I.e., $0x^2 + 0x + 4 = {(A + C)x^2 + (B - 3A)x - 3B + C }$ Thus $0 = A + C$, $0 = B - 3A$, $4 = -3B + C$. $C = -A$, $B = 3A$,\hfil \break $4 = -3(3A) + -A$ implies $4 = -10A$. \hfil \break Hence $A = -{2 \over 5}$, $B = 3(-{2 \over 5}) = -{6 \over 5}$, $C = {2 \over 5}$. \v \centerline{Thus, ${ 4\over (x^2 + 1)(x - 3)} = {-{2 \over 5}x - {6 \over 5} \over x^2 + 1} + {{2 \over 5} \over x - 3}$} \hskip 1.65in = ${-{2}x - {6} \over 5(x^2 + 1)} + {{2} \over 5(x - 3)}$} \eject Linear Functions A function $f$ is linear if $f(a{\bf x} + b{\bf y}) = af({\bf x}) + bf({\bf y})$ Or equivalently $f$ is linear if\hfil \break 1.) $f(a{\bf x}) = af({\bf x})$ and 2.) $f({\bf x} + {\bf y}) = f({\bf x}) + f({\bf y})$ Theorem: If $f$ is linear, then $f({\bf 0}) = {\bf 0}$ Proof: $f({\bf 0}) = f(0 \cdot {\bf 0}) = 0 \cdot f({\bf 0}) = {\bf 0}$ Example 1.) $f:R \rightarrow R$, $f(x) = 2x$ Proof:\hfil \break $f(ax + by) = 2(ax + by) = 2ax + 2by = af(x) + bf(y)$ Example 2.) $f:R^2 \rightarrow R^2$, \centerline{$f((x_1,x_2)) = (2x_1, x_1 + x_2)$} Proof: Let ${\bf x} = (x_1, x_2)$, ${\bf y} = (y_1, y_2) $a{\bf x} + b{\bf y} = a(x_1, x_2) + b(y_1, y_2) = (ax_1, ax_2) + (by_1, by_2) = (ax_1 + by_1, ax_2 + by_2)$ \eject $f(ax_1 + by_1, ax_2 + by_2) $ \hskip 0.4in $= (2(ax_1 + by_1), ax_1 + by_1 + ax_2 + by_2) $ \hskip 0.4in $= (2ax_1 + 2by_1, ax_1 + ax_2 + by_1 + by_2) $ \hskip 0.4in $=(2ax_1, ax_1 + ax_2) + (2by_1, by_1 + by_2) $ \hskip 0.4in $= a(2x_1, x_1 + x_2) + b(2y_1, y_1 + y_2)$ \hskip 0.4in $= af((x_1, x_2)) + bf((y_1, y_2))$ Example 3.) $D:$ {set of all differential functions} $\rightarrow$ {set of all functions}, $D(f) = f'$ Proof: \hfil \break $D(af + bg) = (af + bg)' = af' + bg' = aD(f) + bD(g)$ Example 4.) Given $a, b$ real numbers,\hfil \break $I:$ {set of all integrable functions on [a, b]} $\rightarrow R$ , $I(f) = \int_a^b f$ Proof: $I(sf + tg) = \int_a^b sf + tg = s \int_a^b f + t \int_a^b g = sI(f) + tI(g)$ \eject Example 5.) The inverse of a linear function is linear (when the inverse exists). Suppose $f^{-1}(x) = c$, $f^{-1}(y) = d$. Then $f(c) = x$ and $f(d) = y$ and \hfil \break $f(ac + bd) = af(c) + bf(d) = ax + by$. Hence $f^{-1}(ax + by) = ac + bd = a f^{-1}(x) + bf^{-1}(y)$. Example 6.) $D:$ {set of all twice differential functions} $\rightarrow$ {set of all functions}, $L(f) = af'' + bf' + cf$ Proof: \hfil \break $L(sf + tg) = a(sf + tg)'' + b(sf + tg)' + c(sf + tg) $ \hskip 0.67in $= saf'' + tag'' + sbf' + tbg' + scf + tcg $ \hskip 0.67in $= s(af'' + bf' + cf) +t(ag'' + bg' + cg) $ \hskip 0.67in $= sL(f) + tL(g)$ \eject Consequence 1: If $\psi_1, \psi_2$ are solutions to $af'' + bf' + cf = 0$, then $3 \psi_1 + 5 \psi_2$ is also a solution to \break $af'' + bf' + cf = 0$, Proof: Since $\psi_1, \psi_2$ are solutions to $af'' + bf' + cf = 0$, $L(\psi_1) = 0$ and $L(\psi_2) = 0$. Hence $L(3 \psi_1 + 5 \psi_2) = 3 L(\psi_1) + 5 L(\psi_2)$ \u \hskip 1.24in$ = 3(0) + 5(0) = 0$. \u Thus $3 \psi_1 + 5 \psi_2$ is also a solution to $af'' + bf' + cf = 0$ Consequence 2: \hfil \break If $\psi_1$ is a solution to $af'' + bf' + cf = h$ \hfil \break and $\psi_2$ is a solution to $af'' + bf' + cf = k$, \hfil \break then $3 \psi_1 + 5 \psi_2$ is a solution to $af'' + bf' + cf = 3h + 5k$, Since $\psi_1$ is a solution to $af'' + bf' + cf = h$, $L(\psi_1) = h$. Since $\psi_2$ is a solution to $af'' + bf' + cf = k$, $L(\psi_2) = k$. Hence $L(3 \psi_1 + 5 \psi_2) = 3 L(\psi_1) + 5 L(\psi_2)$ \u \hskip 1.27in$ = 3h + 5k$. \u Thus $3 \psi_1 + 5 \psi_2$ is also a solution to \centerline{$af'' + bf' + cf = 3h + 5k$} Example 7.) The LaPlace transform ${\cal L}$: is linear Theorem: Suppose $f$, $f'$, ..., $f^{(n-1)}$ are continuous and $f^{(n)}$ is piecewise continuous on $0 \leq t \leq A$. Suppose there exists constance $K$, $a$, and $M$ such that $|f(t)| \leq Ke^{at}$, $|f'(t)| \leq Ke^{at}$, ..., $|f^{(n-1)}(t)| \leq Ke^{at}$ for $t \geq M$. Then ${\cal L}(f^{(n)})$ exists for $s > a$ and is given by ${\cal L}(f^{(n)})$ \rightline{$ = s^n{\cal L}(f) - s^{n-1}f(0) - ... - sf^{(n-2)}(0) - f^{(n-1)}(0)$}} LaPlace Transform The LaPlace Transform is a method to change a differential equation to a linear equation. Example: \hfil \break Solve $2y'' + 3y' + 4y = 0$, $y(0) = 5$, $y'(0) = 6$. 1.) Take the LaPlace Transform of both sides of the equation: \vskip 1in 2.) Use the fact that the LaPlace Transform is linear: \vskip 0.4in 3.) Use thm to change this equation into an algebraic equation: ${\cal L}(f^{(n)})$ \rightline{$ = s^n{\cal L}(f) - s^{n-1}f(0) - ... - sf^{(n-2)}(0) - f^{(n-1)}(0)$}} \vskip 1in 3.5) Substitute in the initial values. \vskip 0.5in 4.) Solve the algebraic equation for ${\cal L}(y)$ \vskip 0.2in Some algebra implies ${\cal L}(y) = $ 5.) Solve for $y$ by taking the inverse LaPlace transform of both sides (use a table): \vskip 1in To find the inverse LaPlace transform, you may need to use that the inverse LaPlace transform in linear. You may also need to use partial fractions or other methods in order to right the righthand side of (*) as a sum of functions whose inverse LaPlace transform is known. \v \hrule Calculus pre-requisites you must know. Derivative = slope of tangent line = rate. Integral = area between curve and x-axis (where area can be negative). \eject Integration by parts: Derivative of a product: $(uv)' = uv' + vu'$ \centerline{$uv' = (uv)' - vu'$} \centerline{$\int uv' = \int (uv)' - \int vu'$} \centerline{$\int uv' = (uv) - \int vu'$} Example: $\int e^{2x} sin(3x)$ Let $u = sin(3x)$, $dv = e^{2x}$ then $du = 3cos(3x)$, $v = {1 \over 2}e^{2x}$ then $d^2u = -9sin(3x)$, $\int v = {1 \over 4}e^{2x}$ $\int e^{2x} sin(3x) = {1 \over 2}sin(3x)e^{2x} - \int {3 \over 2}e^{2x}cos(3x)$ \hskip 0.4in $= {1 \over 2}sin(3x)e^{2x} - [{3 \over 4}cos(3x)e^{2x} - \int {-9 \over 4}sin(3x)e^{2x}$ $\int e^{2x} sin(3x) = {1 \over 2}sin(3x)e^{2x} - {3 \over 4}cos(3x)e^{2x} - {9 \over 4}\int sin(3x)e^{2x}$ ${13 \over 4} \int e^{2x} sin(3x) = {1 \over 2}sin(3x)e^{2x} - {3 \over 4}cos(3x)e^{2x}$ $\int e^{2x} sin(3x) = {4 \over 13}[{1 \over 2}sin(3x)e^{2x} - {3 \over 4}cos(3x)e^{2x}]$ \vfill Exercise: Calculate $\int e^{x} cos(2x)$ \end